Answer:
5
Step-by-step explanation:
i think its 2 with the remainder of 8
Answer:
-6/7
Step-by-step explanation:
-4 - 2 = -6
Answer:
$12.50 per hour
Step-by-step explanation:
50/4=12.5
75/6=12.5
Answer:
c,e,d,b,a,
Step-by-step explanation:
nothing is important to me
Answer:
g(h(n)) = 4n² + 12n
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Distributive Property
<u>Algebra I</u>
- Terms/Coefficients
- Function Notation
<u>Algebra II</u>
Step-by-step explanation:
<u>Step 1: Define</u>
g(n) = 4n
h(n) = n² + 3n
g(h(n)) is n = h(n)
<u>Step 2: Find</u>
- Substitute in function h(n) as <em>n</em>: g(h(n)) = 4(n²+ 3n)
- [Distributive Property] Distribute 4: g(h(n)) = 4n² + 12n